Stability of Bacitracin Methylene Disalicylate in the Presence of Pellet Binding Agents in Poultry Feed - Waldroup, P.W.; Watkins, S.E.; Skinner, J.T.; Desai, A.D. (International Journal of Poultry Science, 2001)
A study was conducted with broiler feed medicated with bacitracin methylene disalicylate (BMD) to determine if the addition of lignin sulfonate pellet-binding agents affects the assay of active concentration of BMD in pelleted feed. This study also examined the stability of BMD in the presence of these pellet-binding agents in pelleted feed over extended storage. Diets were mixed that contained 27.5 mg/kg of BMD. Diet 1 did not contain a pellet binder. Diet 2 contained 1.25% Ameri-Bond 2x, and Diet 3 contained 0.6% Pel-Stik. Mash and pelleted samples of each diet were assayed for loss on drying (LOD) and BMD level during week 0. Pelleted samples were stored at ambient temperature (25 oC) and ambient humidity, or elevated temperature (37 oC) and ambient humidity. Samples stored at 25 oC were assayed during weeks 2, 4, 7, 10, and 13, and those stored at 37 oC were assayed during weeks 1, 2, 3, and 4 for LOD and BMD levels. Assay results from week 0 in both mash and pelleted feeds demonstrated the non-interference of the pellet binders with the assay of BMD. The BMD assay results of feeds stored at 25 and 37 oC demonstrated that these pellet binders do not affect the stability of BMD in feed.